2018
DOI: 10.3390/ijerph15102268
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Polar Active Watch and Waist- and Wrist-Worn ActiGraph Accelerometers for Measuring Children’s Physical Activity Levels during Unstructured Afterschool Programs

Abstract: Background: The purpose of this study was to examine the convergent validity of the Polar Active Watch (PAW), a consumer-grade wrist-worn activity monitor, against waist- and wrist-worn research-grade monitors, the ActiGraph GT3X+/GT9X accelerometers, in children. Methods: Fifty-one children (18 boys; mean age = 10.30 ± 0.91 years) wore the three monitors (PAW, GT3X+, and GT9X) during an 80-min afterschool program across five school days. Time spent in sedentary, light-intensity (LPA), and moderate- and vigoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 58 publications
(67 reference statements)
0
25
0
Order By: Relevance
“…The time spent in sedentary (<2 METs), light (2 to 3.99 METs), and MVPA (≥4 METs) [15] were estimated during all waking hours, school hours (8:00 am to 2:45 pm), and non-school hours (i.e., outside of school hours during accelerometer wear time). A previous study reported that the Polar Active watch showed moderate convergent validity for the estimation of physical activity levels in children when compared to other research-grade accelerometers [16].…”
Section: Objectively Measured Physical Activitymentioning
confidence: 91%
“…The time spent in sedentary (<2 METs), light (2 to 3.99 METs), and MVPA (≥4 METs) [15] were estimated during all waking hours, school hours (8:00 am to 2:45 pm), and non-school hours (i.e., outside of school hours during accelerometer wear time). A previous study reported that the Polar Active watch showed moderate convergent validity for the estimation of physical activity levels in children when compared to other research-grade accelerometers [16].…”
Section: Objectively Measured Physical Activitymentioning
confidence: 91%
“…This device records raw accelerations in three axes with a dynamic range ± 6 g at a user-specified sampling frequency (30–100 Hz). Also, the GT3X+ can estimate activity and sedentary bout, PA intensity, and steps taken at a user-selected epoch length (1–60 s) [ 22 ]. The device has been validated for its accuracy in estimating PA compared to the measures from indirect calorimetry in adults and children [ 23 , 24 , 25 ], and has been widely used as a criterion measure for evaluating the validity of consumer-based activity monitors in estimating PA under a free-living condition [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Of the 8 studies, the 2 (25%) remaining studies used the Polar active watch (Polar Electro Oy) [ 40 ] and Movband, Sqord, and Zamzee [ 44 ]. ActiGraph GT3X + (ActiGraph Inc) was most used as a comparison device in free-living settings [ 20 , 39 , 40 ], with both ActiGraph GT9X [ 40 ] and Actiwatch-64 (Philips Respironics) [ 38 ] being used in one study. In controlled settings, WAMs were compared with ActiGraph GT3X+ in 2 studies [ 42 , 44 ], whereas direct observation [ 41 ] and a portable indirect calorimeter (Cosmed K4B2; Cosmed Inc) [ 43 ] were used in one study each.…”
Section: Resultsmentioning
confidence: 99%